Acquired neurogenic foreign accent syndrome after right-hemisphere lesion with left cerebellar diaschisis: A longitudinal study. (September 2020) - Priftis, Konstantinos; Algeri, Lorella; Barachetti, Laura; Magnani, Silvia; Gobbo, Marika; De Pellegrin, Serena
Abstract: Patients affected by acquired neurogenic foreign accent syndrome (ANFAS) start speaking with a new accent that resembles that of a foreign language. ANFAS has been reported following left-hemisphere damage, but it is extremely rare after right-hemisphere damage. We described KKE, a right-hemisphere-damaged patient. His cognitive functions were largely intact and he was not aphasic. Nonetheless, KKE showed a marked foreing accent which was mainly judged as Slavic. Positron emission tomography revealed left cerebellar diaschisis, even if the cerebellum did not appear lesioned, on MRI scans. Remarkably, KKE still showed ANFAS three years after lesion onset. We propose that this very rare variant of ANFAS, after right-hemisphere lesion, can be due to the damage of a complex cerebral network involving supra- and infra-tentorial structures.